An analytical reading in a poem "Two Images" of Abed AlWahab Ismael - Fathe, Faten; ALObeidy, Alaa (Al-Adab Journal, 2023)
The study deals with the poem entitled “Two Images written by the Iraqi poet Abd al – Wahab born and raised in Mosul city. It is one of the most famous poems in his collection [Intuition on a special mirror The poem was chosen carefully to enrich the Iraqi creative production, in addition to the respectable fame of the artist Abd al – Wahab Ismael in the field of Iraqi poetry. The analytical aspect was followed in reading the text and its comparison depending on social and political contexts. the project plan depends on an introduction displaying the importance of identifying the [e reader role in high lightening the situations and their varieties according to the different readings to reach the real semantic understanding of the structure of the text. The study comprises four sections. The first section which is the title identifies the title effect on the text and vice versa with reference to the importance of each in understanding the text semantically the second one tackles (the semantic aspect) of the poem’s sections by making a semantic balance between the two images. The third section determines studying the texts rhythm. revealing the elegant style of the text vocabularies, the fourth section (the lexical aspect) determines the text language which is characterized as a realistic, unambiguous, simple and uncomplex. the research ends up with the main results of the research.